Respuesta :
Step-by-step explanation:
Given
f(x) = 12x + 2
f^-1(x) = ?
Now
Let y = f(x)
or y = 12x + 2
Interchanging the role of x and y
x = 12y + 2
x - 2 = 12y
y = x - 2
12
Therefore f^-1(x) = x - 2
12
Hope it will help you.
Answer:
[tex]f^{-1}[/tex](x) = [tex]\frac{x-2}{12}[/tex]
Step-by-step explanation:
let y = f(x) and rearrange making x the subject, that is
y = 12x + 2 ( subtract 2 from both sides )
y - 2 = 12x ( divide both sides by 12 )
[tex]\frac{y-2}{12}[/tex] = x
Change y back into terms of x
[tex]f^{-1}[/tex] (x) = [tex]\frac{x-2}{12}[/tex]